AUDIENCE PERSPECTIVE ON TODD PHILLIPS’S JOKER (2019): A LACANIAN PSYCHOANALYSIS - Alifiadita Nindyarini Wirawan (Rubikon : Journal of Transnational American Studies, 2021)
The occurrence of American movies which raise psychological issues as part of the main theme often triggers audiences in producing various interpretations. In this respect, the writer chose one of the most popular American movies entitled Joker (2019), directed by Todd Phillips. The movie highlights not only social issues but also psychological issues that engage audiences to produce diverse interpretations, including misinterpretations toward the stereotype of people who suffer mental illness. Therefore, the writer aims to analyze further how the audience perceives and evaluates Joker (2019). Data collected through audiences’ statements in IMDb as an online database of information of films and critical reviews. Psychoanalysis Lacanian: the real, the imaginary, and the symbolic, is applied to comprehending the American audiences response and their interpretations towards Joker (2019) movie. The result of study reveals that audiences’ diverse life experience and background is actually giving major influence towards their interest, response, and interpretations to Joker (2019) movie.